Earnings And Balance Sheet Conservatism In Malaysia: The Influence Of Ifrs, Corporate Governance And Institutional Culture In Malaysia - Marziana Madah, Marzuki (2013)

(untitled)
Recently, two important regulatory reforms initiated by the regulators in Malaysia to enhance financial reporting quality among the public listed companies which are the enforcement of IFRS in 2006 and the amendment of Malaysian Code of Corporate Governance (MCCG) in 2007. Baru-baru ini, dua pembaharuan pengawalseliaan yang penting yang dimulakan oleh pengawal selia di Malaysia untuk meningkatkan kualiti pelaporan kewangan di kalangan syarikat-syarikat senaraian awam iaitu penguatkuasaan IFRS pada tahun 2006 dan pindaan kepada Kod Tadbir Urus Korporat Malaysia (MCCG) pada tahun 2007.